A Case Study on the Usage of the Value Blueprint for Ecosystem Design - Almeida, Luciana; Souza, Cleidson; Lima, Adailton; Reis, Rodrigo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2015)
Ecosystems are an important aspect of today’s software business. Different companies aim to create an ecosystem around their products so that they can benefit from this. Unfortunately, creating such ecosystems is not an easy task. One of the few tools that can be used to facilitate this process is Adner’s Value Blueprint. This tool allows a company to identify the different types of risks that it faces during the establishment of an ecosystem. Adner presents several examples of blueprints he has built and provides some guidelines to create new ones. Given the potential of the approach in addressing some of the issues faced by ecosystem designers, we decided to assess the usage of the Value Blueprint through a case study using data from the Apple Watch ecosystem. We report our results from the Apple ecosystem, and more importantly, our evaluation of the value blueprint tool. We conclude by providing recommendations for practitioners interested in establishing their own ecosystems and researchers interested in the design of ecosystems.